Volatile organic compounds shape belowground plant–fungi interactions - Duc, Nguyen Hong; Vo, Ha T. N.; van Doan, Cong; Hamow, Kamirán Áron; Le, Khac Hoang; Posta, Katalin (Frontiers in Plant Science, 2022)
Volatile organic compounds (VOCs), a bouquet of chemical compounds released by all life forms, play essential roles in trophic interactions. VOCs can facilitate a large number of interactions with different organisms belowground. VOCs-regulated plant-plant or plant-insect interaction both below and aboveground has been reported extensively. Nevertheless, there is little information about the role of VOCs derived from soilborne pathogenic fungi and beneficial fungi, particularly mycorrhizae, in influencing plant performance. In this review, we show how plant VOCs regulate plant-soilborne pathogenic fungi and beneficial fungi (mycorrhizae) interactions. How fungal VOCs mediate plant–soilborne pathogenic and beneficial fungi interactions are presented and the most common methods to collect and analyze belowground volatiles are evaluated. Furthermore, we suggest a promising method for future research on belowground VOCs.